Four newly recorded species of Dryopteridaceae from Kashmir valley, India (Biodiversitas Journal of Biological Diversity, 2014)
Mir SA, Mishra AK, Reshi ZA, Sharma MP. 2014. Four newly recorded species of Dryopteridaceae from Kashmir valley, India.Biodiversitas 15: 6-11. Habitat diversity, elevation, cloud cover, rainfall, seasonal and temperature variations have created many ideal sites for the luxuriant growth of pteridophytes in the Kashmir valley, yet all the regions of the valley have not been surveyed. In Kashmir valley the family Dryopteridaceae is represented by 31 species. During the recent extensive field surveys of Shopian district four more species viz., Dryopteris caroli-hopei Fraser-Jenkins, Dryopteris blanfordii subsp. nigrosquamosa (Ching) Fraser-Jenkins, Dryopteris pulvinulifera (Bedd.) Kuntze and Polystichum nepalense (Spreng) C. Chr. have been recorded for the first time from the valley. The taxonomic description, synonyms, distribution and photographs of each species are given in this article.Key words: Dryopteris, Kashmir valley, Shopian, pteridophytes, new records